Sex, executive function, and prospective memory regulate the chain-mediation pathway of alcohol use and impulsivity - Duan, Fan; Xia, Lingling; Li, Junda; Li, Xiangyu; Zhou, Yiding; Luo, Hanrun; Wang, Ze; Song, Xun; Wang, Jingjing; Chen, Jinxuan; Wang, Yue; Zhang, Jing; et al. (Frontiers in Public Health, 2023)
Objective: Evidence from previous studies indicates that impulsive behaviors are closely linked to alcohol use and misuse and that female drinkers are more impulsive than male drinkers. However, studies investigating the psychological mechanisms of alcohol use and impulsivity based on sex differences are relatively limited.This cross-sectional study comprised 713 residents from 16 cities in Anhui Province, China. Each subject was evaluated for self-reporting measures using several questionnaires, including the general information questionnaire, the Alcohol Use Disorders Identification Test (AUDIT), the Prospective and Retrospective Memory Questionnaire (PRM), the Behavior Rating Inventory of Executive Function-Adult Version (BRIEF-A), and the Barratt Impulsiveness .Results: Executive function and prospective memory may serve as intermediary links between alcohol use and impulsivity. Although the female alcohol usage level was significantly lower than that of males, the female drinkers had more severe executive dysfunction, prospective memory impairment, and impulsivity than male drinkers. Sex moderated the relationship between alcohol use and impulsivity. Furthermore, the indirect effect of executive function, and prospective memory between AUDIT and BIS was more significant in males than in females.Alcohol consumption may be associated with impulsivity formation through executive dysfunction and PM impairment, implying that impulsivity in those with AUD or at risk for AUD might be treated by improving EF and PM. Alcohol use may cause more severe executive dysfunction, PM impairment, and impulsive behaviour in females than in males, and impulsive behaviour in women with AUD was more likely to be due to the direct effects of alcohol consumption, while impulsive behaviour in men with AUD was more likely to be due to the indirect effects of executive dysfunction and PM impairment. These findings provide both clinical and theoretical foundations for addressing issues related to alcohol use.